Why 'spiritism'? - Gyimesi, Júlia (International Journal of Psychoanalysis, 2016)
Some of the early representatives of psychoanalysis had a lifelong interest in certain 'occult' phenomena. Although several theories were born for the purpose of understanding the interest of Sigmund Freud, Carl Gustav Jung or Sándor Ferenczi in spiritualism and related phenomena, interpreters usually ignore the changing cultural meaning and significance of modern occult practices like spiritualism. The aim of the present essay is to outline the cultural and historical aspects of spiritualism and spiritism in Hungary, and thus to shed new light on the involvement of Ferenczi - and other Hungarian psychoanalysts like Géza Róheim, István Hollós, and Mihály Bálint - in spiritualism and spiritism. The connections between spiritualism and the Budapest School of Psychoanalysis will be discussed, highlighting the cultural and scientific significance of Hungarian spiritualism and spiritism in the evolution of psychoanalysis. Taking into account the relative lack of the scientific research in the field of spiritism in Hungary, it can be pointed out that Ferenczi undertook a pioneering role in Hungarian psychical research.
Created from Fastlane, Scopus look-up
Keywords: Hungary; Psychical research; Spiritism; Spiritualism; Sándor ferenczi